Aktivitas Antimikroba Ekstrak Jamur Endofit Kabatiella caulivora var. B yang Diisolasi dari Alyxia reinwardtii BL - NOOR ERMA SUGIJANTO; DIAN ANGGRAENY; NOOR CHOLIES ZAINI (Fakultas Farmasi Universitas Pancasila, 2011)
Endophytic fungi Kabatiella caulivora var B, have been isolated from Alyxia reinwardtii which was collected at Purwodadi Botanical Garden, Pasuruan, East Java. The objective of this present work is to asses the antimicrobial activity from extracts of the endophytic fungi Kabatiella caulivora var B against Bacillus subtilis, Escherichia coli, Salmonella thypi, Pseudomonas aeruginosa, Staphylocooccus aureus and Candida albicans. Disc diffusion method was conducted in this project with two concentration extracts (10 mg/disc and 5 mg/disc). The results showed that the methanol and ethyl acetate extracts of Kabatiella caulivora var B both have antimicrobial activity against all microbial tested, but the methanol extract showed negative activity against Staphylocooccus aureus and Candida albicans at concentration 5 mg. The discovery of endophytic fungi that produces bioactives metabolites has opened a promising new approach to obtain drugs on a commercial scale from microbes that grow inside plants.